The Landscape of Textbook Evaluation Research: A Bibliometric Analysis of Changing Media and Evaluative Approaches - Dianastiti, Firstya Evi; Assidik, Gallant Karunia; Syahroni, Mashud (Jurnal VARIDIKA, 2026)
This study aims to describe performance analysis and co-occurance analysis of “textbook evaluation” keywords based on bibliographic analysis. This research uses quantitative descriptive methods in the form of bibliometric analysis that used the Vosviewer application as the data processor and conducts using the PRISMA method. Research articles collected on the Scopus with a publication period of the last 12 years, from 2013 to 2025. The results of research based on (a) performance analysis and (b) the conceptual structure of the research based on the relationship between keywords The data analysis showed that medical science and language science were the two most researched subjects. Furthermore, from the research findings, it can be concluded that the research trend with textbook evaluation topic has two major themes; textbook content analysis and digital textbooks. The future researchers suggest examining the content of textbooks with changes in students' skills and/or attitudes or evaluating the content of textbooks with a particular learning approach. In terms of digital textbook topics, the development of digital textbooks that utilize the latest technology and the utilization of textbook evaluation is still very possible to be observed.